Ekstraksi minyak atsiri rimpang lengkuas merah (Alpinia purpurata, K.Schum.) metode destilasi uap dan air - Sukardi; Hendrix Yulis Setyawan; Maimunah Hindun Pulungan; Ita Triesna Ariy (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Galangal is one of Indonesia's spice plants and the rhizome contains chemical components, such as essential oils so that it can be used for various purposes, including medicinal, antimicrobial, cosmetic,abd antifungal. The essential oil content of red galangal rhizome is 0.3-1% depending on the quality of the rhizome. The process of extracting essential oils can be done by steam-water distillation. This study aims to determine the effect of temperature and drying time as a preliminary treatment before distillation. The study was designed using a Randomized Block Design with 2 factors: the first is the drying temperature (50oC; 60oC; 70oC), the second factor is the drying time (2; 4; 6 hours). The analysis was carried out yield, refractive index, specific gravity, color, and chemical components. The material used was red galangal rhizome which was approximately 1 year old. Steam and water distillation method was used for oil extraction for 6 hours. The results showed that the best treatment was the control treatment (without drying) with a yield of 0.076%, refractive index 1.4773%, specific gravity 0.8952 (g/ml), color L 23.365, color a* (-)0.995 , and color b* yellowish (+)3.78. Tthe GC-MS, 37 chemical components were detected, of which 6 main components were found with the highest area value, 1.8-Cineole 27.347%; (Z)-beta-Farnesene 11.641%; 2-Beta-Pinene 8.700%; Phenol, 4-(2-propenyl)-acetate (CAS) 6.369%; 3-Cyclohexen-1-ol, 4-methyl-1-(1-methylethyl)-(CAS) 4.305%; and cis-Ocimene 4.009%. The drying reduces the essential oil yield of galangal rhizome.